2009
DOI: 10.1111/j.1365-2095.2009.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial or total replacement of fish meal by local agricultural by-products in diets of juvenile African catfish (Clarias gariepinus): growth performance, feed efficiency and digestibility

Abstract: The study was undertaken to evaluate the growth performance and feed utilization of African catfish, Clarias gariepinus, fed six diets (D) in which fishmeal (FM) was gradually replaced by a mixture of local plant by-products. In diets 1 and 2, FM (250 g kg )1 ) was replaced by sunflower oil cake (SFOC). In diets 3 and 4, FM (250 and 150 g kg )1 , respectively) was replaced by SFOC and bean meal (BM) while FM was totally substituted by a mixture of groundnut oil cake (GOC), BM and SFOC in diets 5 and 6. Sunflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 50 publications
2
31
0
2
Order By: Relevance
“…De acordo com o farelo, tipo de tratamento e antinutriente em questão, foram observados efeitos positivos e negativos. Os teores de antinutrientes encontrados nos farelos não tratados mostraram-se semelhantes aos encontrados por outros pesquisadores (BELL, 1993;GATLIN III et al, 2007;NYINA-WAMWIZA et al, 2010;LOMASCOLO et al, 2012 Observando-se os resultados, fi ca evidenciada a necessidade de se conhecer detalhadamente a composição da matéria-prima a ser tratada, para que seja feita a correta escolha do tipo de solvente. Os métodos de extração ou inativação podem ser efi cientes para a retirada de um ou vários antinutrientes, mas podem, ao mesmo tempo, comprometer a qualidade nutricional do farelo.…”
Section: Resultsunclassified
“…De acordo com o farelo, tipo de tratamento e antinutriente em questão, foram observados efeitos positivos e negativos. Os teores de antinutrientes encontrados nos farelos não tratados mostraram-se semelhantes aos encontrados por outros pesquisadores (BELL, 1993;GATLIN III et al, 2007;NYINA-WAMWIZA et al, 2010;LOMASCOLO et al, 2012 Observando-se os resultados, fi ca evidenciada a necessidade de se conhecer detalhadamente a composição da matéria-prima a ser tratada, para que seja feita a correta escolha do tipo de solvente. Os métodos de extração ou inativação podem ser efi cientes para a retirada de um ou vários antinutrientes, mas podem, ao mesmo tempo, comprometer a qualidade nutricional do farelo.…”
Section: Resultsunclassified
“…affect digestive functions by increasing intestinal flow rates (Lienner 1980, Krogdahl 1989Nyina-Wamwiza et al 2010), which may reduce the retention of dietary nutrients (Krogdahl 1989). This suggested that a 2-fold increase in pumpkin kernel cake in the present study may have affected nutrient absorption, resulting in the lower growth rates of fish fed dietary treatments F2, F3 and F4.…”
Section: Discussionmentioning
confidence: 99%
“…Total carbohydrates was estimated by subtracting crude protein, lipid and ash values from 100. Gross energy [24].…”
Section: Biochemical Analysismentioning
confidence: 99%
“…The economically feasible catfish farming can be achieved when it is based on costeffective feed compound of locally available agricultural by-products [17,22,23]. Many alternatives resources such as feather meal [19], meat and bone meal, hydrolyzed feather meal, fleshings-meal and blood meal [24,25], dried fermented fish by-product silage [6], poultry silage [26], shrimp head waste meal [27,28], poultry by-product meal [2,29], skate meal and sablefish viscera meal [30] have been tried to replace fish meal either partially or fully, but even these meals of various animal sources are not sufficient to meet the growing demands of fish raising industry.…”
Section: Introductionmentioning
confidence: 99%